Antecedents of job satisfaction among academic staff at a Saudi government university: Using partial square - Alharbi, Saleh (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
Abstract The study at hand explores the antecedents of job satisfaction that affect the degree of job satisfaction experienced by academic staff within a government university in Saudi Arabia. This research centers on the nascent University of Tabuk and endeavors to make a contribution that could provide significance to the body of research, especially in the Middle East. The sample of this study consists of 284 academic contractors at the university under study, namely Tabuk University. Smart-PLS Software analyzed the data, and the study revealed that work environment, administrative process, financial incentive and performance appraisal closely interlink with job satisfaction at Tabuk University, with scientific research and publication having little relation to the predictors of JS.